Gender dimensions of community-based management of marine protected areas in Siquijor, Philippines - Clabots, Barbara Michelle (My University, 2013)
This case study focuses on the gender dimensions of the management of community-based Marine Protected Areas (CB-MPAs) in Siquijor, Philippines. The objective of this study is to understand the gender dimensions of CB-MPAs in Siquijor in order to improve MPA management policies. The topic of gender is generally missing from MPA management analyses. A mixed-methods qualitative approach was used. Results indicate that women played a significant role in MPA site selection and management, especially the enforcement of MPA policies and livelihood generation. Further implications for MPA management are that 1) changing gender roles and responsibilities has social equity outcomes, 2) action by gender-progressive individuals enabled women's empowerment, 3) local context can override gender-mainstreaming policies, and 4) a lack of gender considerations in MPA management can undermine long-term success.
Thesis (Master's)--University of Washington, 2013
Keywords: gender; marine protected areas; marine resource management; Southeast Asia; women; Environmental management; Women's studies; Asian studies; marine affairs